INCREASING STUDENTS BASIC SCIENCE PROCESS SKILLS THROUGH THE IMPLEMENTATION OF LEARNING CYCLE 5E MODELS OF CLASS VIII G SMP NEGERI 22 SURAKARTA CLASS YEAR 2012/2013 - Baskoro Adi Prayitno, Aditya H I A, Sri Widoretno (P Biologi FKIP UNS Surakarta, 2015)
The purposes of this research is to increase students basic science process skills of class VIIIG SMP Negeri 22 Surakarta through the implementation of Learning Cycle 5E Models.This research is a Classroom Action Research with 3 cycles of action. Each cycle consisting of 4 phases which is planning, acting, observing, and reflecting. Observational data obtained from the observation, interview, and documentation. Technical analysis of data is technical descriptive both qualitative and quantitative. Data validation is use triangulation method.Result of this research show that with the implementation of Learning Cycle 5E models could increase students basic science process skills and achievement. It?s based on the result of observation. Average percentage for observation skills aspect increase from the 25,93% in pracycle, 42,31% in first cycle, 64,29 % in second cycle and 85,16% in the last cycle. Classification skills increase in each cycle from pracycle to the third cycle that are 22,75%, 39, 01%, 50,55%, 75,27%. Measurement skills increase from the 29,10% in pracycle, 46,15% in first cycle, 62,64% in second cycle, and 80,22% in third cycle. Prediction skills increase from 23,81% in pracycle, 53,85% in first cycle, 62,64% in second cycle, and 81,87% in third cycle. Written communication skills increase from 15,87% in pracycle, 57,14% in first cycle, 69,78% in second cycle, and 81,87% in third cycle. Oral communication skills increase up from 28,04% in pracycle, 40,66% in first cycle, 67,58% in second cycle, and 89,56% in third cycle. Making conclusion skills increase from 23,81% in pracycle, 45,05% in first cycle, 69,23% in second cycle, and 86,26% in last cycle. According to this result, can be concluded that the implementation of Learning Cycle 5E models could increase students basic science process skills student in class VIII G SMP Negeri 22 Surakarta class year 2012/ 2013. Keywords : Learning Cycle 5E, Basic Science Process Skills